Timing and determinants of local residential broadband adoption: evidence from Ireland - Sean Lyons (International Telecommunications Society (ITS), 2010)
This paper tests whether households that are offered broadband service for the first time tend to delay in taking it up. Using cross-sectional data on broadband take-up and socioeconomic characteristics of small areas in Ireland, linked to GIS data on ADSL availability, I find that local adoption rates are positively associated with the time elapsed since service was first offered. The strength of this association increases for the first two years after local enabling of service and then decreases to zero after about five years. The paper also includes estimates of the effect of various household characteristics on adoption, finding effects broadly consistent with previous literature. Simultaneity in demand and supply are addressed using 2SLS regression. Further research will be needed to explain the mechanisms behind lags in adoption behaviour, but those evaluating investments or subsidies in broadband infrastructure should such take lags into account.
Keywords: L96; D12; R22; 330; residential broadband demand; econometric analysis; speed of adoption